Percepção de mães acompanhantes acerca do preparo para alta hospitalar do bebê prematuro : ações da equipe de saúde em unidade de terapia intensiva neonatal - Schmidt, Kayna Trombini (2011)
A descriptive, exploratory, cross-sectional study, a qualitative approach, carried out in a teaching hospital in northwest of Paraná, with the overall objective of knowing how the family of a preterm baby perceived the strategies used by the professional staff during the hospital stay in neonatal units regarding the process of preparation for discharge. We interviewed 12 mothers of preterm infants discharged from the Neonatal Intensive Care Unit (NICU), who, at the time of the interview, were admitted to the Intermediate Care Unit or in the rooms. Only mothers who were effectively assisting their children were included. The interviews were conducted using a semi-structured questionnaire, with the following triggering question: What does caring for the baby mean to you? Data were collected between September 2010 and February 2011. Mothers were approached in two distinctive stages: the first, during the hospitalization of their infants, and the later, with home visits to mothers who lived in the municipality. The statements were submitted to content analysis, according to Bardin's methodological referential. As a complement, the nursing team members who worked in the hospital's neonatology service were also interviewed; nonsystematic and non-participatory observation was also made, in order to better understand the locus of the study, between March and June 2011. A total of nine subjects took part in this stage. The interviews of mothers during their children's hospitalization showed that maternal involvement in the NICU was restricted to touching, talking to the baby and milk-giving through orogastric tube. The main strategy identified by mothers in preparation for discharge was the inclusion of parents in the health care and comforting as soon as the baby was stable and with no need of oxygen. The breastfeeding support was perceived by mothers as an item addressed in an appropriate and incisive way. The welcoming of the nursing staff was also rated positively by mothers, both to strengthen the professional-family bond, and to encourage the maternal stay with their children. In the approach taken with the mothers during home visits, the following problems were observed: lack of information about the vaccination schedule and administration of medications, and the failure of preterm babies' follow-up procedures by the primary care system, emphasizing the need of establishing a more efficient counter-referral flowchart between the hospital and Basic Health Unit responsible for monitoring of these ambulatory patients and families. The maternal absence was mentioned by the professionals as the main difficulty in preparing the family for discharge. Maternal drug addiction and difficulty in understanding the guidelines, generally justified by the low educational level, were scored as discouraging factors by professionals in the education process. The study concluded that the systematization of care through a protocol guide, could contribute to the optimization and upgrading of neonatal care, since the consolidation of a formal strategy may help fill gaps in the teaching/learning process within these units.